Human NADH:ubiquinone oxidoreductase deficiency: radical changes in mitochondrial morphology? - Koopman, Werner J. H; Verkaart, Sjoerd; Visch, Henk Jan; van Emst-de Vries, Sjenet; Nijtmans, Leo G. J; Smeitink, Jan A. M; Willems, Peter H. G. M (American Journal of Physiology: Cell Physiology, 2007)
1 Department of Membrane Biochemistry, Nijmegen Centre for Molecular Life Sciences, 2 Department of Paediatrics, Nijmegen Centre for Mitochondrial Disorders, and 3 Microscopical Imaging Centre of the Nijmegen Centre for Molecular Life Sciences, Radboud University Nijmegen Medical Centre, Nijmegen, The Netherlands Submitted 20 April 2006 ; accepted in final form 10 April 2007 ABSTRACT Malfunction of NADH:ubiquinone oxidoreductase or complex I (CI), the first and largest complex of the mitochondrial oxidative phosphorylation system, has been implicated in a wide variety of human disorders. To demonstrate a quantitative relationship between CI amount and activity and mitochondrial shape and cellular reactive oxygen species (ROS) levels, we recently combined native electrophoresis and confocal and video microscopy of dermal fibroblasts of healthy control subjects and children with isolated CI deficiency. Individual mitochondria appeared fragmented and/or less branched in patient fibroblasts with a severely reduced CI amount and activity (class I), whereas patient cells in which these latter parameters were only moderately reduced displayed a normal mitochondrial morphology (class II). Moreover, cellular ROS levels were significantly more increased in class I compared with class II cells. We propose a mechanism in which a mutation-induced decrease in the cellular amount and activity of CI leads to enhanced ROS levels, which, in turn, induce mitochondrial fragmentation when not appropriately counterbalanced by the cell's antioxidant defense systems. complex I; reactive oxygen species; microscopy; fluorescence Address for reprint requests and other correspondence: P. H. G. M. Willems, 286 Membrane Biochemistry NCMLS, Radboud Univ. Nijmegen Medical Centre, P.O. Box 9101, NL-6500 HB Nijmegen, The Netherlands (e-mail: p.willemsatncmls.ru.nl )